Immunohistochemistry on old archival paraffin blocks: is there an expiry date?. Issue 11 (8th June 2017) - Grillo, Federica; Bruzzone, Martina; Pigozzi, Simona; Prosapio, Stefano; Migliora, Paola; Fiocca, Roberto; Mastracci, Luca
Abstract : Few studies have focused on antigen preservation in formalin-fixed and paraffin-embedded (FFPE) tissue in old archival material and additional studies are required, especially considering that these samples are an irreplaceable resource for scientific and clinical research. The purpose of this study is to verify antigen preservation in FFPE tissue samples stored for several decades. From the pathology archives, FFPE blocks were selected dating back to the 1960s, 1970s, 1980s, 1990s, 2000s and 2010. A panel of 12 antibodies was applied and immunoreactivities were compared. While cytoplasmic antigens showed no reduction in immunostaining intensity over time, membrane and nuclear antigens presented reduced staining intensity in older blocks. In particular, the nuclear antigen, Ki67 and CD31 showed the most pronounced antigen decay in the oldest archival blocks. In order to test possible antigen recovery, deep sectioning and lengthening of heat pretreatment were applied. Both strategies partially recover antigenicity, but their simultaneous application shows the best results.